An Analysis of Learning Activities in the 11th Grade English Textbook Based on Bloom's Taxonomy - Pertiwi, Martiyas; Astiyandha, Tauricha; Tamela, Ellis (Journal of English Language and Education, 2026)
Bloom's Taxonomy plays a very important role in textbooks because it provides a framework for students' thinking, from low to high levels. The purpose of this study is to analyze the extent to which Bloom's Taxonomy between LOTS and HOTS is applied in the learning activities of the SPLASH: Smart Path to Learning English textbook in the field of technology for the Merdeka Curriculum for Grade XI SMK/MAK, published by Erlangga. This study uses a qualitative content analysis approach. The primary data source is the questions in the activity of the grade 11 vocational school English textbook. The results of this study show that the highest percentage of Units 1 to 6 is low cognitive level (LOTS), and the skills that are high in cognitive level (HOTS) are writing and visual representation, where the activities carried out are making a project and presenting the task result.